Temporal regularity of stochastic differential equations driven by G-Brownian motion (Statistics, Optimization & Information Computing, 2024)
This paper is devoted to study the temporal regularity of the solution of stochastic differential equations driven by G-Brownian motion (G-SDEs) under the global Lipschitz and linear growth conditions. In addition, a numerical simulation of a particular G-SDE is provided.